Measurements of volatile organic compounds at two locations in the Northern Colorado Front Range during Spring 2022 - Fischer, Emily V. (Colorado State University. Libraries, 2022)
This dataset was collected by Colorado State University (CSU) graduate students during the spring 2022 semester as part of a course in the Department of Atmospheric Science (ATS-716: Air Quality Characterization). Measurements of volatile organic compounds (VOCs) were collected at two locations in Northern Colorado using low-cost sensors called SENSIT SPODs. The SENSIT SPOD sensor package combines wind field and air pollutant concentration measurements to detect emission plumes and locate the source of those emissions. The sensor measures non-speciated, uncalibrated concentrations of a subset of VOCs. The sensor also measures temperature, relative humidity, pressure, and wind direction and speed. The SPODs were used to trigger the collection of whole air samples during periods with higher concentrations of VOCs. Air samples from the triggered canisters were analyzed at CSU using Gas Chromatography (GC) to provide a measure of approximately 50 VOCs. An integrated canister was used to measure the average concentration of approximately 50 VOCs over a one-week period. After collection, sample air in the canisters was analyzed at CSU using Gas Chromatography (GC).
This dataset contains information on VOC concentration and meteorological conditions collected at the Hearthfire neighborhood (40.638, -105.054) in Fort Collins, CO from February 11, 2022 to April 25, 2022 and the Bella Romero neighborhood (40.405, -104.659) in Greeley, CO from February 23, 2022 to May 5, 2022. At the Hearthfire neighborhood site, triggered canisters were not installed until February 17, 2022. The dataset includes 3 different files: 1) SPOD_PID_Data.zip; 2) Triggered_Canisters.csv; and 3) Integrated_Canisters.csv.
Department of Atmospheric Science
Keywords: volatile organic compounds (VOCs); triggered events; integrated samples; whole air samples; Northern Colorado; air quality; air monitoring; air pollution; community-based research